APPLICATION OF PICTURE STORY BOOKS TO THE EXPRESSIVE LANGUAGE ABILITY OF EARLY CHILDREN - Ajeng Rahayu Tresna Dewi (STKIP Muhammadiyah Kuningan, 2021)
Expressive language is a style of language shown by someone orally where body movements, expressions, and intonation can blend when someone communicates. Even though thought and language are two different aspects, language is an expression of thought that is in line with one's cognitive development. This study aims to obtain information about the expressive language skills of early childhood before and after the application of picture story books to early childhood at Ummu Salimah Kindergarten, Nanggela Village, Kuningan Regency. Preliminary observations at Ummu Salimah Kindergarten show that the stimulation given by the teacher in developing aspects of language, especially expressive language, still needs to be given the right method, namely with the media of picture story books. The method used in this study is a quantitative approach to quasy experimental research. Data analysis techniques in this study include normality tests, homogeneity tests, and hypothesis testing. The results showed that there was a significant difference in expressive language skills between the control class and the experimental class after being treated through picture story books. It is proven that the expressive language skills of children who receive learning using picture story books are better than children who receive conventional learning using the lecture method